The Romanian Prezidentialized Consultative Referendum. Eating Apples from a Poisonous Tree? Personal and Teleological Interpretations (Journal of Legal Studies, 2019)
Through this article, we propose an (original) analytical approach on the consultative referendum of May 2019 and a wider critical landscape regarding the consultative referendum institution by enforcing a teleological interpretation. In this sense, we propose three sections. We will start with a short overview on the use of the consultative referendum in the recent years of Romanian democracy. In the second section we will focus on the consultative referendum from 26 May, 2019. In the third section we will ask the Founding Fathers of the Constitution for an "opinion" regarding the possibilities and impossibilities of the consultative referendum.